2021
DOI: 10.1186/s40168-020-00988-6
|View full text |Cite|
|
Sign up to set email alerts
|

Gut microbiota-derived propionate mediates the neuroprotective effect of osteocalcin in a mouse model of Parkinson’s disease

Abstract: Background Parkinson’s disease (PD) is a neurodegenerative disorder with no absolute cure. The evidence of the involvement of gut microbiota in PD pathogenesis suggests the need to identify certain molecule(s) derived from the gut microbiota, which has the potential to manage PD. Osteocalcin (OCN), an osteoblast-secreted protein, has been shown to modulate brain function. Thus, it is of interest to investigate whether OCN could exert protective effect on PD and, if yes, whether the underlying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 64 publications
4
90
0
Order By: Relevance
“…It was found that fecal microbiota transplantation on a PD mouse model gut reduces microbial dysbiosis, increases striatal neurotransmitters including dopamine and serotonin, and suppresses the activation of astrocytes and microglia in the substantia nigra region of the brain, revealing a neuroprotective effect of fecal microbiota transplantation on PD treatment [ 97 ]. Another study on a PD mouse model demonstrates a neuroprotective effect of propionate, a gut microbial metabolite, on reducing motor deficits and enhancing dopaminergic neurons in PD mice, which may exert its effects through the propionate receptor in the enteric nervous system [ 98 ].…”
Section: Influence Of Gut Microbe-regulated Neurotransmitter Synthesis On Cognitionmentioning
confidence: 99%
“…It was found that fecal microbiota transplantation on a PD mouse model gut reduces microbial dysbiosis, increases striatal neurotransmitters including dopamine and serotonin, and suppresses the activation of astrocytes and microglia in the substantia nigra region of the brain, revealing a neuroprotective effect of fecal microbiota transplantation on PD treatment [ 97 ]. Another study on a PD mouse model demonstrates a neuroprotective effect of propionate, a gut microbial metabolite, on reducing motor deficits and enhancing dopaminergic neurons in PD mice, which may exert its effects through the propionate receptor in the enteric nervous system [ 98 ].…”
Section: Influence Of Gut Microbe-regulated Neurotransmitter Synthesis On Cognitionmentioning
confidence: 99%
“…In addition, the infection of Helicobacter pylori (Hp) has also been reported to be associated with PD [ 15 ]. Moreover, healthy mice receiving gut microbiota transplantation from PD diseased donors showed motor dysfunctions in some research [ 16 18 ]. Collectively, these reports suggest that gut microbiota dysbiosis plays a pivotal role in the pathogenesis of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the microbiome of PD patients is characterized by a decreased abundance of butyrate-producing bacteria with an increased abundance of pro-inflammatory Proteobacteria, which may trigger inflammation-induced misfolding of a-syn [30]. Osteocalcin ameliorates the motor deficits and dopaminergic neuronal loss in PD mice through increasing the potential of microbial propionate production and activating free fatty-acid receptor 3 in enteric neurons [31].…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%